DISABLED BODIES AND STORIED SELVES: AN EXAMPLE OF QUALITATIVE RESEARCH AND NARRATIVE INQUIRY - Smith, Brett (European Journal of Adapted Physical Activity, 2008)
Based on life history data, this qualitative article explores the self-perceptions of a small group of men who, due to a spinal cord injury (SCI) through playing rugby union football, have made a transition from the world of the able-bodied into the world of disability where they remain to this day. The most common kinds of perceptions of self used by the men through telling their stories as they live post-SCI is focused upon in detail. The narrative analyses reveal that three types of narratives help structure and shape the ways in which these men storied their embodied perceptions of self. For the majority of the participants, the restitution narrative was drawn on, and this helped structure a restored self and entrenched self, and was linked to a disciplined body. In contrast, two  people told quest narratives that constitute a perception of a self that is developing and affirmative, and a body that is communicative. For one person, the chaos narrative was foregrounded that resulted in a fragmented self-perception and a chaotic body in action. The implications of all this for disabled people's body-self relationships are critically considered.
Keywords: Disability; Narrative; Self; Body; Sport